Menjadikan Ide Pengayoman Sebagai Asas Penyelenggaraan Lembaga Kepresidenan di Indonesia - Theo Negoro (Fakultas Hukum Universitas Islam Indonesia, 2025)
This article explores the relevance and actualization of the value of pengayoman (protective leadership) as a philosophical and constitutional foundation for strengthening the presidency in Indonesia’s post-Reform era. Rooted in Indonesian legal traditions, particularly through Soepomo’s concept of Manunggaling Kawula Gusti and Sahardjo’s Banyan Tree symbol, pengayoman is framed as an indigenous legal principle where the President acts as the people's protector. Employing a juridical-conceptual and socio-legal approach, the study analyzes how pengayoman, once paternalistic and integralistic, can be recontextualized within a democratic and human rights-oriented presidential system. The findings demonstrate that while Indonesia’s governance model has evolved, the spirit of pengayoman remains relevant as a moral and legal compass for executing presidential power fairly, transparently, and inclusively. This paper also presents normative recommendations for drafting the Presidential Institution Law to embed pengayoman as a constitutional principle, reinforcing the legitimacy and accountability of the presidency today.